AL-MIFTAH LIL ULUM SEBAGAI METODE DALAM MEMPERMUDAH MEMBACA KITAB KUNING DI PONDOK PESANTREN AR-RIDWAN KALISABUK - El Amin, Ahmed Shoim; Nurhayati, Fitri (Jurnal Tawadhu, 2020)
This study uses a qualitative approach, called a qualitative approach because it is a research process that produces descriptive data in the form of written and spoken words from the people the authors observe. Which is done by (3) data collection techniques, namely: observation, interviews and documentation. Technique of data analysis was carried out using qualitative analysis which included data reduction, data display, and conclusion drawing (conclusion).The results of this study indicate that: (1). The application of The Al-Miftah Lil Ulum method in the Ar-Ridwan boarding school is seen from several factors, including: (a). The increase in student learning outcomes is seen from mastery of the material. (b). Can distinguish sentences / lafadz in the yellow book. (c). Read the book according to the rules. (2). The obstacles in implementing the Al-Miftah Lil Ulum method include: (a). Lack of educators. (b). Less effective time. (c). Inadequate facilities and infrastructure.